2013
DOI: 10.1111/jfd.12161
|View full text |Cite
|
Sign up to set email alerts
|

Ichthyophonus‐infected walleye pollock Theragra chalcogramma (Pallas) in the eastern Bering Sea: a potential reservoir of infections in the North Pacific

Abstract: In 2003, the Alaska walleye pollock industry reported product quality issues attributed to an unspecified parasite in fish muscle. Using molecular and histological methods, we identified the parasite in Bering Sea pollock as Ichthyophonus. Infected pollock were identified throughout the study area, and prevalence was greater in adults than in juveniles. This study not only provides the first documented report of Ichthyophonus in any fish species captured in the Bering Sea, but also reveals that the parasite ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…An expansive area exists between the two southernmost sampling locations in this study (Puget Sound and San Francisco Bay), and Pacific herring populations throughout this gap tend to be relatively small; however, it is likely that Ichthyophonus occurs in some of these stocks, as the parasite can occur in high prevalence among another clupeid, American shad (Alosa pseudoharengus), from the Oregon/ Washington boarder . Although these results indicate that Pacific herring represent a dominant host species for Ichthyophonus in the NE Pacific, other species appear to maintain the parasite northward into the Bering Sea, where a paucity of infections in Pacific herring (Kocan et al 2004) are replaced by oftenhigh prevalences in Chinook salmon and walleye pollock (White, Morado & Friedman 2014). The geographic extremes of the Ichthyophonus range in Pacific herring likely shift on an interannual basis in response to changing climatic conditions, ocean circulation patterns, water temperatures and invertebrate assemblages.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…An expansive area exists between the two southernmost sampling locations in this study (Puget Sound and San Francisco Bay), and Pacific herring populations throughout this gap tend to be relatively small; however, it is likely that Ichthyophonus occurs in some of these stocks, as the parasite can occur in high prevalence among another clupeid, American shad (Alosa pseudoharengus), from the Oregon/ Washington boarder . Although these results indicate that Pacific herring represent a dominant host species for Ichthyophonus in the NE Pacific, other species appear to maintain the parasite northward into the Bering Sea, where a paucity of infections in Pacific herring (Kocan et al 2004) are replaced by oftenhigh prevalences in Chinook salmon and walleye pollock (White, Morado & Friedman 2014). The geographic extremes of the Ichthyophonus range in Pacific herring likely shift on an interannual basis in response to changing climatic conditions, ocean circulation patterns, water temperatures and invertebrate assemblages.…”
Section: Discussionmentioning
confidence: 82%
“…Although these results indicate that Pacific herring represent a dominant host species for Ichthyophonus in the NE Pacific, other species appear to maintain the parasite northward into the Bering Sea, where a paucity of infections in Pacific herring (Kocan et al . ) are replaced by often‐high prevalences in Chinook salmon and walleye pollock (White, Morado & Friedman ). The geographic extremes of the Ichthyophonus range in Pacific herring likely shift on an interannual basis in response to changing climatic conditions, ocean circulation patterns, water temperatures and invertebrate assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, the Alaska walleye pollock industry reported product quality issues attributed to an unspecified parasite in fish muscles. Using molecular and histological methods, White and coauthors [44] identified the parasite in Bering Sea pollock as Ichthyophonus.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ichthyophonus is known to infect many marine fishes, its known host distribution in the marine waters of Alaska is limited to Pacific herring in the Gulf of Alaska, walleye pollock Gadus chalcogrammus in the Gulf of Alaska and Bering Sea, Chinook salmon in the Yukon and Kuskokwim rivers, and Pacific halibut Hippoglossus stenolepis in Prince William Sound, Cook Inlet, and the eastern Bering Sea (Eaton et al 1991, Marty et al 1998Kocan et al 2004, White et al 2014, Hershberger et al 2018. The presence of Ichthyophonus in these fishes, all of which are important prey species at some point in their life histories, suggests that many other predatory fishes in the region are likely exposed to the parasite through trophic in teractions.…”
Section: Introductionmentioning
confidence: 99%